Proposição e validações de equações para estimativa da erosividade de dois municípios do estado de São Paulo - da Silva, Reginaldo Barboza [UNESP]; Iori, Piero; Silva, Francisca Alcivania de Melo [UNESP] (My University, 2009)
The equations and extrapolation use to localities whose characteristics of soil and climate, even if partial, distinguish the town to which they were generated, still permeate in studies to estimate the rainfall erosivity (EI 30). This work has objective to propose and validate mathematical equations to estimate the rainfall erosivity of two cities of Sao Paulo State's. The adjusted to estimate obtaining and validate data of equations of erosivity (EI 30) according to values of coefficient of rain (Rc) were obtained from pluviographic and pluviometric rainfall data, respectively, using of distinct historical rainfall series. Mutiple comparisions test and confidence intervals were performed to compare absolute average of EI 30, pluviometric data (Pp), and Rc. The correlation between EI 30 and Rc was verified by of Pearson correlation coefficient. Test of the hypothesis of equality between population variance was used to compare the equations. Pluviometrics data of historical series rainfall data different than those that the models were generated were used to validate and to assess the performance of the equations, proposed of this study and compare them with another equation already consolidated in literature. The results show that for the conditions under which the study was conducted, the simple linear equations, shown to be the most appropriate to estimate the rainfall erosivity these two cities. According to the test of the hypothesis of equality variances between populations, the equations adjusted for each city differ statistically so that the rainfall erosivity of each city must be estimated by their respective equation.
Proposition and compare of equations to estimate the rainfall erosivity in two cities of São Paulo state
Keywords: Erosion; Modeling; USLE; Vale do Ribeira; correlation; erosion control; erosivity; hypothesis testing; model validation; numerical model; rainfall; soil erosion; Universal Soil Loss Equation; urban area; Brazil; Ribeira Valley; Sao Paulo [Brazil]